Optimizing the gelation, structure, and thermal stability of alkali-induced duck egg white gels with calcium chloride - Pin-Chun Tseng; Wen-Yuan Yang; Yi-Chen Chen; Yen-Po Chen; Jia-Shian Shiu; Sheng-Yao Wang (Poultry Science)
Alkali treatment is a proven method for producing transparent elastic protein gels and could provide a practical way to utilize surplus duck egg whites that are generated during processing. However, this method often leads to gel liquefaction and structural instability. The addition of metal cations at appropriate concentrations can enhance the stability and strength of the gels and prevent liquefaction. The aim of this study was to investigate the effects of calcium chloride on the formation and thermal stability of alkali-induced duck egg-white gels using fresh duck egg whites. The results indicated that egg whites treated with 0.05 % and 0.10 % calcium chloride exhibited significantly accelerated gelation rates and enhanced elastic modulus. However, a calcium chloride concentration of 0.20 % notably retarded the gelation process (p < 0.05). Gels containing 0.10 % and 0.20 % calcium chloride demonstrated significantly higher Bloom strength, reduced free thiol content, and lower free alkalinity after 40 h at room temperature compared to the control group (p < 0.05). Upon heating, these calcium-containing gels exhibited improved thermal stability. Calcium ions, which are safer than other metal cations, contributed to maintaining the gel's soft-solid state during heat treatment, enhanced its appearance, reduced free thiol content, and decreased free alkalinity. The addition of calcium ions at appropriate concentrations enhances the gelation rate, structural integrity, and thermal stability of alkali-induced duck egg white gels and offers a safe and efficient method for utilizing surplus duck egg whites. The results of this study could provide a foundation for the development of calcium-enriched preserved-egg production.